Peripheral Nervous System : Interrelationships and Variations - Matejčík, Viktor; Haviarová, Zora; Kuruc, Roman (Springer Nature Switzerland AG, 2024)
This book comprehensively evaluates the morphological and clinical aspects of the peripheral nervous system and its involvement in various pathologies. It thoroughly describes its topography, morphology, its peculiarities - that are missing in anatomical and surgical textbooks- and their possible influence on the clinical picture. Their preoperative diagnosis is difficult, even impossible. Figures and line drawings enrich the view of structures that so far. have only been partially documented. The authors' descriptions are based on clinical observations and systematic work on the 246 human bodies of healthy people who died a sudden or violent death (most often in car accidents). Dissection is the most precise method to elucidate the range of variability, which is often largely responsible for the failure of surgical treatments. Their recognition can minimize damage to nerve structures, and the acquired knowledge can help clarify clinical signs and symptoms in surgery or internal medicine.